Characteristics of consumers influencing adoption behavior for XBRL - Rawashdeh, Awni; Selamat, Mohamad Hisyam; Abdullah, Mohd Syazwan (2011)
This paper empirically examines the impact of demographic factors upon the XBRL adoption among consumers, the six demographic characteristics that provide insights to XBRL adopters and non-adopters, as they were identified from the literature review used in this study. These included age, gender, education, experience and type of industry. The data on these variables was collected on a global scale employing an online survey. A self-administered questionnaire was positioned on the home page of the XBRL network web site with a total of 68 responses obtained from the respondents. The findings of this research suggest that the four variables of age, gender, experience, type of industry and country significantly differentiated the adopters from the non-adopters of the XBRL, whilst education was found to be non-significant. The implications of the findings are discussed in the context of promoting the adoption of XBRL technology.